Alloy‐Mediated Ultra‐Low CO Selectivity for Steam Reforming over Cu−Ni Bimetallic Catalysts. Issue 18 (24th July 2018) - Ma, Kui; Cui, Zhonghui; Zhang, Zhitao; Huang, Jingjing; Sun, Zhirui; Tian, Ye; Ding, Tong; Li, Xingang
Abstract: Steam reforming of simple oxygenated hydrocarbons without C−C bonds is suitable for small‐scale decentralized H2 production for fuel cells. However, the relatively high CO concentration in H2 ‐rich reformates produced by traditional Cu‐based catalysts will poison the Pt‐based anode in fuel cells. Here, we describe a new approach to the design of Cu−Ni bimetallic catalysts based on nickel‐phyllosilicate for steam reforming of dimethyl ether (DME). With the tunable formation of the Cu−Ni alloy, we can modulate the selectivity of CO and CH4 in steam reforming and achieve H2 ‐rich reformates with an ultra‐low concentration of CO (below 1000 ppm). This process only requires simple and low‐energy purification pretreatments to meet the requirements of commercial fuel cells. Mechanistic studies reveal that the Cu−Ni alloy can adsorb CO, particularly at high temperatures, and simultaneously suppress CO dissociation to methane. Abstract : Blowing off steam : This paper describes a new approach of designing Cu−Ni bimetallic catalytic systems for dimethyl ether/methanol steam reforming. The Cu−Ni system exhibits an interesting alloy‐mediated selectivity of CO and CH4, thereby producing hydrogen‐rich reformates with an ultra‐low CO concentration (<1000 ppm), which could be commercially potential for fuel cells.